PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATERI HUKUM NEWTON UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Afrianto, Fahrizal; ', Yennita; ', M. Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to improve student’s critical thinking skill at class X SMAN Plus Riau Province through Problem Based Learning model on Newton Law subject. The design was pre-experimental with one-group pretest-posttest design. The sample were students of class X MIA 3. Data were obtained from pretest, and posttest. The result of this research showed the the improvement of students critical thinking skill through Problem Based Learning model. The improvement occured on each aspect of critical thinking skill such as: (a) Elementary clarification; (b) Basic support; (c) Inference; (d) Advance clarification; (e) Strategy and tactics. The results showed that average N-Gain for all critical thinking aspect score was on medium category. Therefore, it can be concluded that Problem Based Learning model was able to improving student’s critical thinking skill.Keywords: critical thinking skill, problem based learning, newton law